2009
DOI: 10.1007/s10495-009-0442-7
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in pre-Bilaterians: Hydra as a model

Abstract: Hydra is a member of the ancient metazoan phylum Cnidaria and is an especially well investigated model organism for questions of the evolutionary origin of metazoan processes. Apoptosis in Hydra is important for the regulation of cellular homeostasis under different conditions of nutrient supply. The molecular mechanisms leading to apoptosis in Hydra are surprisingly extensive and comparable to those in mammals. Genome wide sequence analysis has revealed the presence of large caspase and Bcl-2 families, the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 66 publications
2
90
0
1
Order By: Relevance
“…Lasi et al . (2010) showed that transient expression of FoxO‐GFP protein induced an apoptosis rate of 20–60% in Hydra epithelial cells. Conversely, co‐expression of one of the Hydra insulin‐like genes with the FoxO‐GFP protein was shown to decrease the rate of apoptosis in these cells.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lasi et al . (2010) showed that transient expression of FoxO‐GFP protein induced an apoptosis rate of 20–60% in Hydra epithelial cells. Conversely, co‐expression of one of the Hydra insulin‐like genes with the FoxO‐GFP protein was shown to decrease the rate of apoptosis in these cells.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Conversely, co‐expression of one of the Hydra insulin‐like genes with the FoxO‐GFP protein was shown to decrease the rate of apoptosis in these cells. As the IIS acts through the PI3K/AKT/SGK pathway, one can hypothesize that the IIS reduces Hydra ′s FoxO activity (Lasi et al ., 2010). …”
Section: Animal Modelsmentioning
confidence: 99%
“…In the colonial hydrozoan Hydractinia echinata, it is necessary for metamorphosis [11,12]. Recent genome sequencing projects have indicated the presence of large families of apoptotic proteins, including caspases, Bcl-2 family proteins and APAF-1 in cnidarians [13][14][15]. However, their functional interactions and the roles they have in apoptosis are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The first and most direct way to inhibit cell death was to prevent caspase activity in regenerating Hydra: for this purpose animals were treated for a short period of time (90 minutes before amputation and up to 90 minutes after) with the Z-VAD-fmk pan-caspase inhibitor (Graczyk 2002). Previous studies performed by the group of Charlie David and Angelika Boettger in Munich had proven that the genetic circuitry supporting apoptosis is well conserved across eumetazoans, and that indeed caspase inhibitors significantly reduce caspase activity in Hydra (Cikala et al 1999;Lasi et al 2010). This short exposure to Z-VAD-fmk was sufficient to efficiently inhibit apoptosis: 75% of the bisected animals exposed to Z-VAD-fmk no longer regenerate their head and actually die within the next days.…”
Section: Injury-induced Apoptosis Is Necessary For Head Regenerationmentioning
confidence: 99%